Quantitative assessment and mechanism analysis of modification approaches for cold recycled mixtures with asphalt emulsion. (10th November 2021) - Dong, Shi; Wang, Decai; Hao, Peiwen; Zhang, Qing; Bi, Jiefu; Chen, Wenfu
Abstract: Cold recycled mixtures with asphalt emulsion (CRMEs) are environmentally friendly and cost-effective materials widely used in asphalt pavement maintenance and rehabilitation (M&R). However, CRMEs exhibit lower mechanical performance and durability than hot-mix asphalt. This study aims to evaluate the effects of different modification approaches on the mechanical properties and durability of CRMEs. To this end, four optimal additives, including the rejuvenation agent (RA), basalt fibres (BFs), styrene–butadiene rubber (SBR) latex, and Buton rock asphalt (BRA), were added to CRMEs during the mixing procedure. Comprehensive laboratory tests including immersion splitting and freeze–thaw splitting tests, high-temperature rutting tests, low-temperature semi-circle bending tests, and indirect tensile fatigue tests were conducted to evaluate the mechanical properties of the modified CRMEs. In addition, the radar chart method was performed to quantitatively assess the effects of the multiple modification approaches. To investigate the influence mechanisms, microscopic features of the modified CRMEs, such as the compactness of the mortar and bonding sufficiency of the interface, were detected by scanning electron microscopy. The results showed that the addition of RA, SBR latex, and BRA can improve the comprehensive performance of the modified CRMEs. Among these additives, RA had the most significant effect, followed by BRA. These findings aid in selecting modifiers to improve the performance and durability of CRMEs in practical engineering applications. Graphical abstract: Image 1 Highlights: Comprehensive performances of different modified asphalt emulsion cold recycled mixes. Quantitative assessment of the modified effects on mechanical properties and durability. Mechanism analysis of different modification approaches through multi-scale tests. Recommendation suitable approaches based on actual application requirements.